Public Health and Microbiological Evaluation of Enhanced Recovery after Surgery (ERAS) Protocols in Hysterectomy Patients: A Clinical Study - Zubia Bugti, Shahnela Raza, Ayesha Taj, Nazia Jameel, Hassan Raza Heral, Sadia Ahmad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Enhanced Recovery After Surgery (ERAS) protocols are evidence-based perioperative pathways designed to optimize surgical outcomes, reduce postoperative complications, and improve recovery. However, limited data exist regarding their impact on microbiological outcomes and infection control among hysterectomy patients in developing healthcare settings. Objective: To evaluate the public health and microbiological effects of ERAS protocols compared with conventional postoperative care in women undergoing elective hysterectomy. Methods: This multicenter clinical study was conducted at the Department of Gynaecology, Unit I, SPHQ/BMCH Quetta, and the Department of Obstetrics & Gynaecology, Liaquat National Hospital Karachi from January 2022 to May 2023. A total of 120 patients were enrolled and allocated into ERAS (n=60) and conventional care (n=60) groups. Clinical outcomes included postoperative pain, time to oral intake, mobilization, length of hospital stay, and surgical site infection (SSI) rates. Microbiological evaluation included wound swab cultures, organism identification, and colony-forming unit (CFU) quantification. Results: ERAS patients demonstrated significantly shorter hospital stays (2.4 ± 1.0 vs. 4.8 ± 1.4 days), lower SSI rates (6.7% vs. 28.3%), earlier oral intake (4.3 ± 2.1 vs. 18.5 ± 6.4 hours), and earlier mobilization (11.2 ± 3.6 vs. 27.3 ± 7.2 hours) compared with conventional care. Pain scores were significantly reduced in the ERAS group (3.0 ± 1.2 vs. 6.1 ± 1.7). Microbiological assessment showed fewer pathogenic isolates, absence of MRSA, and lower mean CFU counts in the ERAS group (2.0 × 10³ CFU/mL vs. 7.5 × 10³ CFU/mL). Conclusion: ERAS protocols substantially improve postoperative recovery and infection control in hysterectomy patients. The significant reduction in SSI rates, bacterial load, hospital stay, and antibiotic use underscores ERAS as an effective clinical and public health strategy. Routine integration of ERAS pathways into gynecological surgical care is strongly recommended to enhance patient outcomes and promote antimicrobial stewardship. Keywords: Enhanced Recovery After Surgery, Hysterectomy, Surgical Site Infection, Microbiological Evaluation, Public Health, ERAS Protocols, Gynecologic Surgery.